2020
DOI: 10.1093/biolre/ioaa177
|View full text |Cite
|
Sign up to set email alerts
|

Development of assisted reproductive technologies forMus spretus

Abstract: The genus Mus consists of many species with high genetic diversity. However, only one species, Mus musculus (the laboratory mouse), is common in biomedical research. The unavailability of assisted reproductive technologies (ARTs) for other Mus species might be a major reason for their limited use in laboratories. Here, we devised ARTs for Mus spretus (the Algerian mouse), a commonly used wild-derived Mus species. We found that in vitro production of M. spretus embryos was difficult because of low efficacies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is also important to note that the IVF rate when using M. spretus sperm was found to be significantly lower than seen when using C57BL/6J sperm, potentially because the Infrafrontier protocols used are optimized for the C57BL/6J strain. Potentially, new protocol improvements in assisted reproductive techniques optimized for M. spretus may help improve these rates 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the IVF rate when using M. spretus sperm was found to be significantly lower than seen when using C57BL/6J sperm, potentially because the Infrafrontier protocols used are optimized for the C57BL/6J strain. Potentially, new protocol improvements in assisted reproductive techniques optimized for M. spretus may help improve these rates 12 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that use of pseudopregnant ICR females as recipients did not compromise development of chimeric embryos. We have previously reported that transfer of embryos from the MSM strain and SPR2 ( M. spretus ) into laboratory females needed cyclosporin A, an immunosuppressant, or (B6 × C3H) recipient females to avoid immuno-rejection by mothers 32 , 33 . It was probable that the origin of the placenta from laboratory mice in our chimeric mice could minimize the immunological attack from the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although it is possible that the sperm cryopreservation process might skew the success of assisted reproduction methods in general, it is encouraging that the extensive biomedical and research use of cryopreserved, and banked, mouse spermatozoa (where ICSI is widely preferred as the fertilization method) do not appear to have produced the range of problems seen with fishes and amphibians [ 114 , 115 ].…”
Section: Art and Human Infertility Treatmentmentioning
confidence: 99%